The determinants of individual perception towards debit card product consumption in Malaysia / Adilah Md. Nor - Md. Nor, Adilah (Faculty of Business and Management, 2011)
The purpose of this exploratory research is to explore the link between the choices of using debit card product as a medium of payment. It examines the Malaysian market in relation debit card usage and its impact on individual perception. Furthermore, the study aims to identify the keys that determine the individual perception towards debit card product consumption.